Anaemia among primary care patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD): A multicentred cross-sectional study - Idris I.; Tohid H.; Muhammad N.A.; Ahad A.M.; Ali N.; Sharifuddin N.; Aris J.H.; Mohd Radzniwan A Rashid (BMJ Publishing Group, 2024)
Indexed by WOS/Scopus/ERA